Traversability analysis with vision and terrain probing for safe legged robot navigation - Haddeler, Garen; Chuah, Meng Yee (Michael); You, Yangwei; Chan, Jianle; Adiwahono, Albertus H.; Yau, Wei Yun; Chew, Chee-Meng (Frontiers in Robotics and AI, 2022)
Inspired by human behaviors when traveling over unknown terrain, this paper proposes the use of probing strategies and integrates them into a traversability analysis framework to address safe navigation on unknown rough terrain. Our framework integrates collapsibility information into to our existing traversability analysis, as vision and geometric information alone could be misled by unpredictable non-rigid terrains such as soft soil, bush area, or water puddles. With the new traversability analysis framework, our robot has a more comprehensive assessment of unpredictable terrain, which is critical for its safety in outdoor environments. The pipeline first identifies the terrain's geometric, semantic properties using an RGBD camera and identifies desired probing locations on questionable terrains. These regions are probed with a force sensor to determine the risk of the terrain collapsing when the robot steps over it. This risk is formulated as a collapsibility metric, which estimates an unpredictable region's ground collapsibility. Thereafter, the collapsibility metric, together with geometric, and semantic spatial data are combined and analyzed to produce global and local traversability grid maps. These traversability grid maps tell the robot whether it is safe to step over different regions of the map. The grid maps are then utilized to generate optimal paths for the robot to safely navigate to its goal. Our approach has been successfully verified on a quadrupedal robot in both simulation and real-world experiments.